Macroanatomic investigations on the branches of the internal iliac artery in kangal dogs - Hakan Yalçın; Zafer Daşçı; Nejdet Dursun (Eurasian Journal of Veterinary Sciences)
Twelve adult healthy Kangal Dogs [Turkish Shepherd Dog) of male (6) and female (6), 2-4 years old, weighting 18-20 kg were used in this study. Red latex was injected to common carotid artery. Following this, the internal iliac artery were dissected. It was determined that the internal iliac artery came to an end leaving to the caudal gluteal and internal pudendal arteries at the level of the a!a ossis ilii. It was observed that the umblical artery reached to the side bound of the urinary bladder and onginated as Ihe lig teres vesicae at the level of the internal iliac artery its origin. It was determined that the caudal gluteal artery ended separating between the semitendinosis and semimembranosus muscles and, its originated as another from the last two branches of the internal iliac artery at the level of the ala ossis ilii. The internal pudendal artery is another from the last two branches of the internal iliaca artery. It was observed that the internal pudendal artery originated from the level of Ihe lor. ischiadicum minor.